Biophysics - Glaser, Roland; SpringerLink (Online service) (1999)
The message of this book is that biophysics is the science of physical principles underlying the "phenomenon life" on all levels of organization. Rather than teaching "physics for biologists" or "physical methods applied to biology", it regards its subject as a defined discipline with its own network of ideas and approaches. The book starts by explaining molecular structures of biological systems, various kinds of atomic, molecular and ionic interactions, movements, energy transfer, self organization of supramolecular structures and dynamic properties of biological membranes. It then goes on to introduce the biological organism as a non-equilibrium system, before treating thermodynamic concepts of osmotic and electrolyte equilibria as well as currents and potential profiles. It continues with topics of environmental biophysics and such medical aspects as the influence of electromagnetic fields or radiation on living systems and the biophysics of hearing and noice protection. The book concludes with a discussion of system analyses, including models of neural processes as well as of ecological interactions, growth, differentiation and evolution.
1 Nature and Subject of Biophysics -- 2 Molecular Structure of Biological Systems -- 3 Energetics and Dynamics of Biological Systems -- 4 Physical Factors of the Environment -- 5 The Kinetics of Biological Systems -- References.
PB
Keywords: Life sciences; Human physiology; Biochemistry; Cytology; Environmental protection; Life Sciences; Biochemistry, general; Biophysics and Biological Physics; Human Physiology; Effects of Radiation/Radiation Protection; Cell Biology